Bankruptcy of Lehman Brothers: Determinants of Cross-country Impacts on Stock Market Volatility - Kim, Daehwan; Song, Chi-Young (International Journal of Economics and Financial Issues, 2017)
We empirically examine the determinants of the short-term cross-country impacts of Lehman Brothers’ bankruptcy on the volatility of stock prices. According to the results of this study, countries with lower financial openness and greater stock market depth experienced a smaller increase in stock price volatility. This suggests that capital control and greater stock market development were relatively more useful in maintaining the stability of stock markets at the time of Lehman’s failure. On the other hand, we find little evidence for the role of international imbalances, trade openness, economic sizes and income levels, and macroeconomic fundamentals. Keywords: Lehman Brothers; volatility of stock prices; financial openness; stock market development JEL Classifications: F32; F36; F38; F41